Strategi Penyuluh Agama Islam dalam Meningkatkan Pemahaman Agama Masyarakat di Kota Medan - Wikanda, Fauji (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The objective of this article to find out the strategy of the Islamic counseling in increasing people`s understanding in religion in Medan. The sampling technique in this study used the technique of Snowball sampling. The researcher selects the informants according to the sample category by following the suggestions and recommendations of the key informants, followed by the informants appointed by the key informants. Regarding the performance of extension workers in the Ministry of Religion of Medan City, the author directly met the Chair of the Pokjaluh Ministry of Religion of Medan City as the key informant. The method in this study uses a qualitative approach, namely the descriptive method. The problem is focused on the strategy of Islamic religious instructors in increasing religious understanding of the people in the city of Medan. Data collection techniques through triangulation techniques. namely comparing observation information, interviews with the contents of related documents. Based on the analysis and the data in the field, it is found that, first, Islamic counseling consists of 8 (eight) specializations – eradicating the Koran alliteration, halal products, radicalism and splinter groups, peaceful family, HIV/AIDS & drung, zakat (charity), waqf, and reconciliation of religius people; secondly, the strategy of Islamic counseling in increasing people`s understanding religion in medan has been successful.